2017
DOI: 10.1002/jso.24687
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term adverse effects after retropubic and robot‐assisted radical prostatectomy. Nationwide, population‐based study

Abstract: Background and ObjectivesSurgery for prostate cancer is associated with adverse effects. We studied long‐term risk of adverse effects after retropubic (RRP) and robot‐assisted radical prostatectomy (RARP).MethodsIn the National Prostate Cancer Register of Sweden, men who had undergone radical prostatectomy (RP) between 2004 and 2014 were identified. Diagnoses and procedures indicating adverse postoperative effects were retrieved from the National Patient Register. Relative risk (RR) of adverse effects after RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
(56 reference statements)
0
17
1
1
Order By: Relevance
“…In contrast, laparoscopic or open surgery usually uses between four and six interrupted sutures to approximate the bladder and urethra . As a result, there is likely to be a higher incidence of urinary leakage from the VUA, which can result in increased scarring/fibrosis around the anastomosis, with subsequent stricture formation . Furthermore, when performing RARP, a posterior reconstruction (Rocco) suture is often placed, which is another step often not performed during either LRP or ORP.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, laparoscopic or open surgery usually uses between four and six interrupted sutures to approximate the bladder and urethra . As a result, there is likely to be a higher incidence of urinary leakage from the VUA, which can result in increased scarring/fibrosis around the anastomosis, with subsequent stricture formation . Furthermore, when performing RARP, a posterior reconstruction (Rocco) suture is often placed, which is another step often not performed during either LRP or ORP.…”
Section: Discussionmentioning
confidence: 99%
“…The online version of this article (https ://doi.org/10.1007/s1002 9-020-02178 -7) contains supplementary material, which is available to authorized users. * H. Nilsson hanna.nilsson@vgregion.se Extended author information available on the last page of the article an increased risk of developing an incisional hernia after RALP as compared to RRP, despite the longer incision of the latter [8,10,11,13]. Inguinal and incisional hernia may infrequently cause severe morbidity, and even mortality [14,15].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…It has been suggested that it is the lower midline incision that induces the inguinal hernia formation and that all surgery performed by a lower midline incision could cause this complication [6]. Today a majority of prostate cancer operations are performed using robot-assisted laparoscopic technique (RALP) and hence several authors have addressed the question whether the risk of postoperative inguinal hernia is increased to the same extent after robot-assisted laparoscopic radical prostatectomy, reporting diverging results [5,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that minimally invasive methods (LRP or RALP) display lower cumulative PIH rates compared to RRP [8,9]. Nevertheless, a Nationwide, large population-based study demonstrated that no signi cant difference was found in risk of PIH between RRP and RALP with 11,212 patients [10]. Risk factors including age, body mass index (BMI) previous history of hernia or abdominal surgery, prostate volume pelvic lymph node dissection (PLND) incontinence outcome, operative time, surgeon experience and patent processus vaginalis have been studied to be presumably associated with PIH previously [11][12][13][14], but no consensus was reached due to various inclusion criteria and population heterogeneity.…”
Section: Introductionmentioning
confidence: 99%